an ion beam complement to electron beam writers - Bruchhaus, Lars (Technische Universität Dortmund, 2012)
With the technology expertise from complementary fields, we have managed to develop a new liquid metal ion source (LMIS) focused ion beam (FIB) instrument dedicated to nano patterning. It possesses an acceleration voltage regime up to 40 kV. The instrument is a commensurate alternative nano patterning tool which has enabled us to explore a large amount of successful application fields. In our experiments we have exploited also additional ion-matter interactions to the two current main stream ones (sputtering and gas assisted processing). For example employing 40 keV Ga ions, we have analysed two applications in more detail: We exposed a 6 nm thin hydrogen silsesquioxane (HSQ) resist and reached a line-width thinner than 10 nm as well as a minimum period of 30 nm. In addition we exploited the instrument patterning strategies flexibility to analyse a long known minimum line-width limiting effect in LMIS resist exposure. Thin films of Au55 clusters were exposed as a potential candidate for process complexity reduction in nano fabrication of conducting features. Further promising results are summarised proving the instrument stability and applicability.
a part of the development, characterisation and utilisation
Keywords: Au55; charged particle optics; FIB; focused ion beam; gold cluster; HSQ; IBL; ion beam lithography; ion matter interactions; liquid metal ion source; LMIS; nano patterning; nanostructures; nanostructuring; 530; Ionenstrahllithographie; Nanolithographie